2008
DOI: 10.1016/j.neuropsychologia.2008.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Charting the acquisition of semantic knowledge in a case of developmental amnesia

Abstract: We report the acquisition and recall of novel facts by Jon, a young adult with early onset developmental amnesia whose episodic memory is gravely impaired due to selective bilateral hippocampal damage. Jon succeeded in learning some novel facts but compared with a control group his intertrial retention was impaired during acquisition and, except for the most frequently repeated facts, he was also less accurate in correctly sourcing these facts to the experiment. The results further support the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 14 publications
3
43
1
1
Order By: Relevance
“…It has been proposed that the learning of semantic associations can bypass the hippocampus entirely and, instead, rely on the ATL (63). Discrete hippocampal damage slows the learning rate of semantic associations but does not impair it completely (64). Indeed, individuals with hippocampal damage can learn new semantic associations through a type of incidental learning called "fast mapping," whereas patients with ATL lesions cannot (65).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the learning of semantic associations can bypass the hippocampus entirely and, instead, rely on the ATL (63). Discrete hippocampal damage slows the learning rate of semantic associations but does not impair it completely (64). Indeed, individuals with hippocampal damage can learn new semantic associations through a type of incidental learning called "fast mapping," whereas patients with ATL lesions cannot (65).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Vargha-Khadem, Gadian, Watkins, Connelly, Van Paesschen, W., et al (1997) demonstrated that patients with developmental amnesia can show a very good level of semantic knowledge, acquired in childhood and adolescence, despite significant impairment in episodic learning. A more recent study of one of these patients (Jon) showed that he can learn new facts, but that his inter-trial retention was impaired relative to controls (Gardiner, Brandt, Baddeley, Vargha-Khadem, & Mishkin, 2008). In Korsakoff patients, Pitel, Beaunieux, Guillery-Girard, Witkowski, de la Sayette, et al (2009) argued for a 2-route theory of new semantic learning (cf.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting, highly structured, information system is termed 'semantic memory' (Patterson et al, 2007;Tulving, 1985) and is thought to depend on networks comprising widespread cortical regions (Binder et al, 2009;Martin and Chao, 2001). Various observations suggest that the formation of semantic memories depends in large part on episodic memory (Moscovitch et al, 2005;Rosenbaum et al, 2001; but see Gardiner et al, 2008 for an opposite viewpoint) and an intact hippocampus (Bayley and Squire, 2005;Hayman et al, 1993;Manns et al, 2003). Episodic memory refers to memory for events and situations, organized in an autobiographical stream, and rich in contextual information (Tulving, 1983).…”
Section: Introductionmentioning
confidence: 99%